The Implementation Of Modern Cryptography On Document Data Security - Triza Randes Syafutra; Khairil Khairil; Eko Suryana (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
The aspect of data security has become a very important aspect of an information system. Many people start looking for ways to secure data or information, because global computing has become insecure and often escapes the attention of computer users and is starting to become a very serious issue. So, we need a way to secure confidential and important data. One of the cryptography methods that can be used is the RSA method. The RSA algorithm is one of the most popular public key algorithms used and is still used today. The strength of this algorithm lies in the exponential process, and factoring a number into 2 prime numbers which until now has taken a long time to factorize. The implementation of the system used the Visual Basic 2010 programming language and the method used in this research is an applied research method. Where the results of the tests that have been carried out are obtained where the RSA Algorithm can provide additional security to the document, this is because the text data owned by the user will be encrypted and replaced with a row of numbers that does not represent the contents of the original data.